Efektifitas Media Cerita Bergambar (CERGAM) terhadap Pengetahuan, Sikap dan Tindakan Siswa PAUD/TK - Witradharma, Tetes Wahyu; Jumiyati, Jumiyati (Politeknik Kesehatan Tanjung Karang, 2019)
The low consumption of vegetables and fruits in the community requires an Eat Vegetables and Fruit Campaign as an effort to reach the Nutrition Conscious Family, especially in school-age children and adolescents as the nation's successors. The research objective was to determine the effectiveness of drawing story media to knowledge, attitude, and behavior of kindergarten. The study used a quasi-experiment study, with a non-randomized control group pre-test - post-test design. Research location in Puskesmas Padang Serai Bengkulu City. The population is kindergarten students. Sampling using the non-probability method with purposive sampling technique totaling 60 samples. Data were analyzed by univariate, bivariate dependent t-test/Wilcoxon test, independent t-test/Mann Whitney and covariance analysis test. The results showed that there were differences in knowledge, attitudes, and behavior in the treatment and control groups, furthermore the drawing story media was effective to knowledge, attitude, and behavior of kindergarten students. Educate by using drawing story media continuously as an effort to increase the knowledge, attitude, and behavior of kindergarten students. Elaborate drawing story media with more interesting storylines and colorful images.